2020
DOI: 10.1177/0004867420969810
|View full text |Cite
|
Sign up to set email alerts
|

When to initiate antipsychotic treatment for psychotic symptoms: At the premorbid phase or first episode of psychosis?

Abstract: Objective: Antipsychotic drugs are widely used for treating patients with first episode of psychosis, targeting threshold psychotic symptoms. The clinical high risk of psychosis is characterized as subthreshold psychotic symptoms and it is unclear whether they can also benefit from antipsychotic drugs treatment. This study attempted to determine whether initiating antipsychotic drugs treatment in the clinical high risk of psychosis phase was superior to initiating antipsychotic drugs treatment in the first epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…However, we cannot exclude that for some patients, the prescription of an antipsychotic drug might prompt a sensibilization of the dopamine receptors, which may favour a further rebound of symptoms until conversion to psychosis (Chouinard et al, 2017 ). In‐depth scrutiny of the symptoms' profile is thus necessary to wisely ponder the best, individualized treatment option for UHR patients (Zhang, Xu, Tang, et al, 2020 ; Zhang, Xu, Wei, et al, 2020 ), balancing psychopharmacotherapy with psychotherapy approaches, such as cognitive‐behavioural therapy, which offers first‐line protection from conversion to psychosis (Devoe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we cannot exclude that for some patients, the prescription of an antipsychotic drug might prompt a sensibilization of the dopamine receptors, which may favour a further rebound of symptoms until conversion to psychosis (Chouinard et al, 2017 ). In‐depth scrutiny of the symptoms' profile is thus necessary to wisely ponder the best, individualized treatment option for UHR patients (Zhang, Xu, Tang, et al, 2020 ; Zhang, Xu, Wei, et al, 2020 ), balancing psychopharmacotherapy with psychotherapy approaches, such as cognitive‐behavioural therapy, which offers first‐line protection from conversion to psychosis (Devoe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In analysing data from the ShangHai At Risk for Psychosis (SHARP) study, Zhang, Xu, Tang, et al ( 2020 ) found that UHR patients who did not receive antipsychotics showed a lower conversion rate than those who did (17.7% vs. 26.9%; odds ratio = 0.66; 95% confidence interval [CI] = 0.44, 0.98). Moreover, patients who initiated antipsychotic drugs whilst at clinical high risk of psychosis had lower remission rates than those who initiated antipsychotic drugs when already in the first episode of psychosis (Zhang, Xu, Wei, et al, 2020 ). In a meta‐analysis of 14 studies that reported detailed information on antipsychotics prescription in UHR patients, Raballo et al ( 2020b ) found that UHR patients who had received a prescription of antipsychotics before entering the programme of care (n = 112) had a higher relative risk (RR) of conversion to psychosis (29% vs. 16%; RR = 1.47; 95%CI: 1.18–1.83) than those who did not have received any (n = 235).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a recent study (Fusar-Poli et al, 2020a) demonstrated that CHR individuals who developed psychosis (despite antipsychotic treatment) had worse outcomes compared with patients who initially presented in first-episode groups. Our previous study (Zhang et al, 2020) provided evidence that early use of antipsychotics for the CHR population may be effective in reducing the severity of positive symptoms; however, this may not be the best approach in terms of long-term remission.…”
Section: Discussionmentioning
confidence: 99%